Crystalline nephropathy caused by tosufloxacin. Issue 11 (November 2016) - Matsubara, Risa; Kibe, Tetsuya; Nomura, Takemasa
Abstract: A 14‐year‐old girl was treated for 3 days with tosufloxacin (450 mg twice a day) for acute bronchitis and then developed acute kidney injury. Renal ultrasound showed enlarged kidneys without hydronephrosis. Urinalysis indicated drug crystal casts (2–3/HPF), consistent with drug‐induced crystalline nephropathy. The patient recovered gradually with i.v. hydration and discontinuation of tosufloxacin, leading to the diagnosis of tosufloxacin crystalline nephropathy. Medical practitioners should be aware that crystalline nephropathy can occur in pediatric patients receiving tosufloxacin.